The Role of Teacher Psychological Leadership in Building Relationships with Students at Al-Irsyad IT Middle School Jember - Barirotus Saadah; Rizky Yunita; Mu’alimin Mu’alimin (Khalifah : Jurnal Pendidikan Nusantara, 2024)
This journal discusses the important role of teachers as psychological guides in building strong relationships with students to achieve effective classroom management. Teachers are not only responsible for delivering learning material, but also for understanding and helping students overcome various psychological problems that can hinder their learning process. Building strong relationships with students can be done in various ways, such as: Show empathy and concern. So teachers need to show that they care about students as individuals, not just as learners. Create open and supportive communication. Likewise, teachers must provide space for students to feel comfortable in sharing their thoughts and feelings. By building strong relationships with students, teachers can create a safe and conducive learning environment, so that students feel more motivated and involved in the teaching and learning process. This can ultimately increase the effectiveness of classroom management and achieve optimal learning goals.